The use of probiotic for growth and survival of milkfish (Chanos chanos Forskal) - Abdul Rakhfid; Wa Ode Nanny Kulsum; Fendi; Mosriula; Muhammad Bakri; Karyawati; Alimin; Rochmady (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2020)
Milkfish cultivation in Muna Regency has not yet developed optimally, allegedly due to poor water circulation. Internal solution that can be done is the use of probiotics in water maintenance media. The aim of this study was to determine the effect of adding proiotics to media water with different doses on the growth and survival of milkfish (Chanos chanos Forskal), carried out in May to June 2019 at the Gonangkalo Beach Fish Seed Center (BBIP), Gonebalano, Duruka District, Muna Regency. The study used a complete randomized design (CRD) with three probiotics namely A 10 mL treatment per container, 20 mL treatment B per container and 30 mL C treatment per container. Data were analyzed using Variance Analysis (ANOVA) at 95% confidence level (α 0.05). The results showed that the highest daily growth rate was obtained in Treatment B at 5.84±0.16% per day followed by Treatment A at 5.71±0.23% per day and Treatment C at 5.42±0.10% per day. The highest absolute growth of milkfish was obtained in Treatment B at 8.24±0.28 g per individual and the lowest was in Treatment C at 7.95±0.0.33 g per individual, Continuation in Treatment A and B 83.33±5,77%, while in Treatment C 80.00±10.00%. Analysis of variance (α 0.05) showed that the use of probiotics with different doses significantly affected absolute growth (p>0.011) but did not significantly affect the daily growth rate (p<0.063) and survival (p<0.850) of milkfish